Problematika Fungsi Hakim Pengawas dan Pengamat Dalam Sistem Peradilan Pidana Indonesia: Tinjauan Studi Socio-Legal - H Muhamad Rezky Pahlawan MP; Chessa Ario Jani Purnomo (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2020)
In this study, the author considers 3 (three) reasons that are considered important such as philosophical aspects, aspects of criminal law theory, and political aspects of national criminal procedural law after describing 5 (five) previous legal scientific studies related to the implementation of supervisory judges and observers in the criminal justice system. This study aims to reflect on the legal principles of the kimwasmat institution and build models and patterns of implementing the kimwasmat institution. This research intends to answer 2 (two) legal issues: firstly, what are the legal principles contained in Article 280 of the KUHAP. Secondly, what is the model and pattern of implementation of the supervisory and observer judge institutions based on Article 280 of the KUHAP. This legal research uses the socio-legal research method, the materials of which are the results of interviews of judges in deliberate district courts, study of court official documents, relevant laws and regulations to legal issues, legal theory and social science theories. This study found, firstly, the function of kimsmat based on the principle of legal certainty and the principle of benefit which seeks to be married into the principle of certainty which is useful based on Pancasila. Finally, the classical bureaucratic model and the institutional model as well as the aspects of state administration to explain the management and control functions of the authority of the kimwasmat become the basis for the court to carry out criminal objectives.